Analisis Pengaruh Karakteristik Perusahaan dan Tata Kelola Perusahaan terhadap Modal Intelektual - Anita Anita; Trifni Trifni (Universitas Internasional Batam, 2021)
Intellectual capital provides good information in investment choices. This study aims to determine whether firm size, profitability, leverage, liquidity, audit committee size, and board of commissioners' composition have an influence on intellectual capital in companies listed on the Indonesia Stock Exchange. The existing design in this study has a quantitative character. The objects in this study are companies listed on the Indonesia Stock Exchange from 2015-2019. The results of the research firm size, profitability, liquidity, and the composition of the board of commissioners have a significant impact on intellectual capital. Meanwhile, leverage and audit committee size do not have a significant impact on intellectual capital.